Lessons from a crisis-opportunities for lasting public health change from the COVID-19 pandemic - Jaskanwal Deep Singh Sara (Frontiers Media S.A., 2022)
The coronavirus 2019 (COVID-19) global pandemic has wrought hardship and disrupted lives across all strata of humanity, giving rise to a variety of social, psychological, and medical challenges to individuals in almost every country in the world. Yet for all the difficulties the pandemic has inflicted, it has forced us to examine previously accepted practices at home, work, and society more broadly and has led to innovative changes in the way we communicate and collaborate. These novel approaches to contemporary challenges were devised primarily to allow continued productivity despite the need for social distancing, but have offered secondary advantages that could provide society with lasting benefits. In the following review, we outline three aspects of working life and public health which could experience lasting improvement on the back of lessons learnt from the current crisis.